Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Kreativitas Belajar IPAS Siswa Kelas V Sekolah Dasar - Lestari, Eva Rini; Halidjah, Siti (AS-SABIQUN, 2023)
This study aims to determine the increase in learning creativity of IPAS grade V elementary school students by applying the Project Based Learning (PjBL) learning model. This type of research is a Classroom Action Research (PTK) which includes several cycles. The research flow using the Kemmis & Mc Tanggart model consists of four stages, namely, 1) planning, 2) implementation, 3) observation, and 4) reflection. The subjects of this research were students of class VB SD Negeri 36 Pontianak Kota with a total of 27 students. The instruments of this research were observation sheet of learning creativity and documentation study. Data collection techniques were observation, creativity assessment rubric, and documentation. Data analysis techniques used in this study were descriptive quantitative and descriptive qualitative. The results of the pre-cycle average value of the percentage of student learning creativity of 25% (very low creativity), cycle I average value of the percentage of student learning creativity has increased by 49.7% (low creativity), cycle II average value of the percentage of student learning creativity of 66.44% (moderate creativity), and cycle III average value of the percentage of student learning creativity has increased dramatically by 80.55% (high creativity). Based on the research that the application of the Project Based Learning (PjBL) learning model can increase IPAS learning creativity.